Measuring Patient-Reported Health-Related Quality of Life in Velopharyngeal Insufficiency: Reliability and Validity of the Brazilian Portuguese Version of the VELO Instrument. (October 2019) - Denadai, Rafael; Raposo-Amaral, Cassio Eduardo; Sabbag, Anelise; Ribeiro, Rafael Andrade; Buzzo, Celso Luiz; Raposo-Amaral, Cesar Augusto; Hung, Man; Skirko, Jonathan R.
Objective: To test the Brazilian Portuguese velopharyngeal insufficiency (VPI) Effects on Life Outcome (VELO) instrument for reliability and validity. Design: Cross-sectional methodological study. Setting: Tertiary craniofacial medical center. Participants: Participants with VPI (VPI group, n = 60), with cleft and without VPI (no VPI/cleft group, n = 60), and with no cleft nor VPI (no VPI/no cleft group, n = 60) and their parents (n = 180). Interventions: All patients with VPI 8+ years old and their parents completed the Brazilian–Portuguese VELO instrument and other questionnaires (Pediatric Quality of Life Inventory4.0, PedsQL4.0; Pediatric Voice-Related Quality of Life, PVRQOL; and Intelligibility in Context Scale, ICS) at baseline; patients with VPI and their parents completed the VELO instrument again 2 weeks later. Main Outcome Measures: The VELO instrument was tested for internal consistency, test–retest reliability, discriminant validity (participants with VPI against participants with no VPI), concurrent validity against other questionnaires, criterion validity against hypernasality severity, and construct validity against nasal air emission and overall velopharyngeal competence (speech construct) and velopharyngeal gap (anatomic construct). Results: The VELO had excellent internal consistency (Cronbach α 0.99 for parents and 0.98 for participants with VPI) and test–retest reliability (all intraclass correlation coefficient > 0.87). The VELO discriminated well between VPI group and unaffected groups (all P < .05). The VELO was significantly correlated with the PedsQL 4.0, PVRQOL, and ICS (– r > 0.75; P < .001). The VELO met criterion validity, speech construct validity, and anatomic construct validity ( r > 0.7; P < .001). Conclusions: The Brazilian-Portuguese VELO instrument demonstrated reliability (internal consistency and test–retest) and validity (discriminant, concurrent, criterion, and construct).